Nickel Extraction from Laterite Ore via Sulfuric Acid Leaching and Iron Precipitation Using NaOH with Gravimetric Analysis - Ardiansah, Ardiansah; Albar J, Muh. Azis; Aldi, Aldi (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2025)
The global demand for nickel has continued to rise, in line with the growth of the stainless steel industry and renewable energy technologies. Indonesia, as one of the countries with the largest reserves of laterite nickel ore in the world, faces challenges in processing limonite ore, which typically contains high levels of iron and lower concentrations of nickel. This study aims to improve the efficiency of nickel extraction through a hydrometallurgical approach, using sulfuric acid (H₂SO₄) leaching, selective iron precipitation with sodium hydroxide (NaOH), and nickel determination using the gravimetric method. The leaching process was conducted at 90°C, varying the leaching time and acid concentration, followed by iron precipitation through pH adjustment and the addition of hydrogen peroxide to oxidize Fe²⁺ to Fe³⁺, which subsequently forms Fe(OH)₃. The resulting iron-free filtrate was then reacted with dimethylglyoxime (DMG) to form a pink precipitate of the nickel complex [Ni(DMG)₂], which was then analyzed gravimetrically. The results showed that increasing leaching time and solvent concentration significantly enhanced the nickel extraction percentage. This approach proved to be effective in improving the selectivity and efficiency of nickel separation from impurities, thereby supporting a cleaner and more sustainable nickel production process.